Right Cerebral Hemispheric Hypoperfusion Caused by Type A Aortic Dissection and Intramural Hematoma - Jun Young Chang; Jeong-Ho Hong; Jin-Heon Chung; Min-Ju Yeo; Moon-Ku Han (Journal of Neurocritical Care, 2014)
Background: Acute aortic dissection typically manifests severe abrupt chest or back pain which can be accompanied by various neurologic symptoms. However, in case without typical pain, the accurate diagnosis is very difficult. Case Report: A 77-year old female patient presented with symptoms of right cerebral hypoperfusion such as altered mental status, left sided hemiplegia and hypesthesia, tonic-clonic movement and right sided gaze deviation. Initial brain CT angiography revealed a dissection of ascending aorta and intramural hematoma compressing the origin of common carotid artery. Perfusion brain CT showed the prolonged time to peak and mean transit time for right cerebral hemisphere. Emergent replacement of ascending aorta and hemiarch was done without complication. Conclusion: Cerebral hemispheric hypoperfusion could be initial manifestations of the aortic dissection. Aortic dissection should be discriminated in a patient with neurologic deficit accompanied by atypical systemic symptoms.